Prenatal pembrolizumab exposure as the potential link among recurrent necrotizing enterocolitis, neonatal diabetes mellitus and exocrine pancreatic insufficiency: a case report - Pasquale Castaldo; Luigi Altimari; Maria Grazia Capretti; Giulio Maltoni; Andrea Scozzarella; Vittoria Paoletti; Luigi Corvaglia; Arianna Aceti (Italian Journal of Pediatrics)
Abstract Background Necrotizing enterocolitis (NEC) is a serious complication predominantly affecting very low birth weight neonates, characterized by high mortality and long-term morbidity. Neonatal diabetes mellitus (NDM) is a rare condition with diverse etiologies, including genetic predisposition and autoimmune mechanisms. To our knowledge, NEC and NDM have never been previously reported together. Case presentation We report the clinical case of a late preterm infant whose mother had received an immune checkpoint inhibitor treatment (pembrolizumab) for metastatic gastric cancer during pregnancy. The infant suffered from severe and recurrent necrotizing enterocolitis (NEC), neonatal diabetes mellitus (NDM) and exocrine pancreatic insufficiency that required a multidisciplinary approach. Prenatal exposure to pembrolizumab might explain the co-occurrence of the three diseases and the complex and unusual medical history of the child, even if the possibility that these events were independent of each other cannot be totally ruled out. Conclusion This case suggests the potential association between antenatal pembrolizumab exposure and severe neonatal comorbidities. Furthermore, it highlights the challenge of managing concurrent NEC, NDM and exocrine pancreatic insufficiency in early infancy, emphasizing the need for multidisciplinary care and long-term follow-up to address complex clinical and developmental outcomes.